Analisis Faktor-Faktor yang Mempengaruhi Permintaan Man Terpilih di Propinsi Daerah Istimewa Yogyakarta(Analyze of The Factors that Influence Demand of Special Fishery Product in Yogyakarta Special Region Province - Agus Setiadi; Irham Irham (Agro Ekonomi, 2003)
This experiment was conducted to determine factors that influence the demand of spesial fishery product in Yogyakarta Spesial Region Province. This experiment was used freshwater catfish and tuna small fish as object of experiment. Factors involved in demand function of tuna small fish in Yogyakarta Special Region Province are own price, freshwater catfish price, rice price, soybean price, cooking oil price, chicken price, egg chicken price, goat meat price, income percapita, inhabitant of Yogyakarta Spesial Region Province, dummy variable (0=non crisis period, 1=crisis peeriod) and freshwater fish price. Factors were analyze demand function of freshwater catfish are own price, tuna small price, rice price, soybean price, cooking oil price, chicken price, egg chicken price, goat meat price, inhabitant Yogyakarta Spesial Region Province, income percapita, dummy variable (0=non crisis period, 1=crisis peeriod) and freshwater fish price The conclusion result taken out from this study may contribute fishers a contructive information to become a base of opinion on demand of fishery product in Yogyakarta Spesial Region Province.It use secondary time series datas, datas taken from the the fishery service statistic of the Yogyakarta Spesial Region Province and Biro of Statistic Center Yogyakarta Spesial Region Province, datas which are produced along the period 1980-2000. Analyze model applied here is the demand function expressed in ordinary least square (OLS) by natural logarithm (ln).The conclusion result shown that the function demand of tuna small fish was significantly influence by own price, freshwater catfish, and cooking oil price while freshwater fish, chicken meat price, chicken egg price, rice price, income percapita and dummy variabel are not influence demand function of tuna small fish significantly. Cross elasticity of freshwater catfish and cooking oil are positive so freshwater catfish and cooking oil are subtitute to tuna small fish.The conclusion result shown that the demand function of freshwater catfish was significantly influence by own price, tuna small fish price, chicken meat price, goat meat price and chicken egg price while the others factors i.e cooking oil price, soybean price, inhabitant Yogyakarta Spesial Region Province, income percapita and dummy variable are not significantly influence the demand function of freshwater catfish. Cross elasticity of chicken meat, goat meat, chicken egg, and tuna small fish are positive so chicken meat, goat meat, chicken egg, and tuna small fish are subtitute to freshwater catfish.